Negros de pele clara: construção de identidades negras no YouTube - Dantas, Luiz Gustavo de Jesus (2023)
This work deals with the theme of the construction of black identities on YouTube. The objective is to discuss how light-skinned black YouTubers construct and reverberate representations of their black identities, based on discourses about themselves and blackness in Brazilian culture. It also aims to reflect on the political and sociocultural imbrications that influence the issue of black identity in Brazil, specifically with regard to light-skinned black people, as well as problematize the role of YouTube in this process, as an alternative for mobilization and resistance. Methodologically, a bibliographical research will be carried out, in addition to contente and representational analysis, taking the understanding of the orisha Exu as an analytical sensitivity. We centered our work on three channels that produced videos in which issues about light-skinned black black people were directly addressed: Afros e Afins, by Nátaly Neri; Muro Pequeno, by Murilo Araújo; and Spartakus Santiago, wich carries tha name of its presenter.